Tru-cut biopsy in cryptogenic organizing pneumonia - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2015)
Cryptogenic organizing pneumonia (COP) was first described by Davison and colleagues in 1983. Previously, it was called bronchiolitis obliterans organizing pneumonia (BOOB). The following are known causes of COP: toxic gas inhalation, chemotherapy, radiation therapy, aspiration, blood transfusion, upper respiratory tract infections, or it can be idiopathic. The clinical features of the patients resemble those of pneumonia or upper respiratory tract infection. In COP, imaging scans of the lungs reveal diffuse migrating patchy infiltrations which are in contact with the pleura. Corticosteroids are the first choice for treatment, but in some patients other immunosuppressive drugs are needed. Low doses may result in relapses. Transbronchial biopsy has a low yield in the diagnosis, instead tru-cut biopsy is the first choice for a definitive diagnosis. In this paper, we define our experience with two patients from whom we obtained a tru-cut lung biopsy in order to reach for a diagnosis.
Keywords: Cryptogenic organising pneumonia; Tru-cut; biopsy; LUNG; CT; ASPIRATION; NEEDLE